Shaping medieval markets - Dijkman, Jessica (2011)
In the late Middle Ages the county of Holland experienced a process of uncommonly rapid commercialisation. Comparing Holland to England and Flanders this book examines how the institutions that shaped commodity markets contributed to this remarkable development.